Comparison of the effects of three different Baccaurea angulata whole fruit juice doses on plasma, aorta and liver MDA levels, antioxidant enzymes and total antioxidant capacity - Ibrahim, Muhammad; Mikail, Maryam Abimbola; Ahmed, Idris Adewale; Hazali, Norazlanshan; Abdul Rasad, Mohammad Syaiful Bahari; Abdul Ghani, Radiah; Hashim, Ridzwan; Arief Ichwan, Solachuddin Jauhari; Md Isa, Muhammad Lokman; Draman, Samsul (Springer Berlin Heidelberg, 2018)
Purpose Baccaurea angulata (common names: belimbing dayak or belimbing hutan) is a Malaysian underutilized fruit. The preliminary work on B. angulata fruit juice showed that it possesses antioxidant properties. Therefore, further work is needed to confirm the efficacy and proper dosage of B. angulata as a potential natural antioxidant. The present study was thus carried out to compare the effects of three different B. angulata whole fruit (WF) juice doses administered at nutritional doses of 0.50, 1.00 and 1.50 ml/kg/day on plasma, aorta and liver malondialdehyde (MDA) levels, antioxidant enzymes (superoxide dismutase, glutathione peroxidase and catalase) as well as total antioxidant capacity in rabbits fed high-cholesterol diet. Methods Thirty-five male rabbits of New Zealand strain were randomly assigned to seven groups. For 12 weeks, group CH was fed 1% cholesterol diet only; group C1 was fed 1% cholesterol diet and 0.50 ml/kg/day B. angulata WF juice; group C2 was fed 1% cholesterol diet and 1.00 ml/ kg/day B. angulata WF juice; group C3 was fed 1%